The childbirth and breastfeeding experiences of primigravidas who attended childbirth education classes - Irmin B Segeel; Diana du Plessis (AOSIS, 2006)
Knowledge brings with it power, confidence and courage. It is important to prepare for childbirth not only physically, but also emotionally and psychologically. Opsomming Kennis gaan gepaard met mag, selfvertroue en dapperheid. Dit is dus belangrik om nie net fisiek nie, maar ook emosioneel en sielkundig op die bevalling voor te berei. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.